(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Fin Tech (Financial Technology) and Block chain are highly discussed topics among technology leaders in finance today. This article describes the impact and revolution of Fin Tech and Block chain in the financial industry and demonstrates the main characteristics of such technology. However, the development of Block chain is still an ongoing process. Some challenges have arisen, such as scalability, security, privacy, latency, etc. It is important for financial markets to have a better understanding of the Block chain industry and find robust solutions. Therefore, this paper can demonstrate an overview of the Block chain and its development in the financial services and investigate challenges for adaptation of the technology.